Road traffic noise control based on maximum noise levels and individual vehicle emissions - Rylander, Ragnar; Sörensen, Stefan (Proceedings from the Annual Transport Conference at Aalborg University, 2005)
Dose-response relationships for road traffic noise exposure and the extent of annoyance are reviewed with focus on the maximum noise levels. Measurements from different streets with typical city traffic are evaluated, using the maximum noise from individual vehicles as the dose descriptor and a basis for possible reductions in the extent of annoyance. Suggestions for actions to improve noise control and decrease the extent of annoyance are presented.